Functional status untrained and physical activity teenagers as a reflection of the quality of life (based heart rate variability) - I. V. Mylnikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The study of functional status in 122 boys aged 16,5 ± 1,5years, with varying intensities of physical activity. Given that the autonomic nervous and cardiovascular systems reflect adaptive reserve capacity of the organism, functional status was assessed by heart rate variability using the device «VNSmikro-3» (OOO «Neurosoft», c. 1vanovo). Optimal generation of heart rate (111 type of heart rhythm regulation) was observed in 75,0 % of boys with low, 68,8 % moderate and 38,9 % of high-intensity exercise. Rhythmogram persons of this type of regulation reflect the impact of a balanced system of generating units heart rate. 1ndividuals with type 1 regulation of heart rate were observed inyoung men with low (3,6 %) and moderate (8,3 %) intensity of physical activity, indicates an increase in activity of s^rasegmental component of the cardiac rhythm generation. People with type 11 regulation of heart rate observed in the group of young men with low (7,1 %) and moderate (5,3 %) intensity. Features rhythmogramsyoung men with type 11 regulation of heart rate is the predominance of: central regulation and low values of the spectral characteristics, the presence of extreme tension of the cardiovascular and autonomic nervous systems. Adolescents with type 1V regulation found among young men with moderate (12,5 %), low (16,7 %) and high (61,1 %) intensity of physical activity. 1n physically active boys availability of this option demonstrates the regulation of over-training will occur and the body, a possible violation of the sinus node automaticity. Found that the functional effects of a regulatory system are: 25 % of young men with low-intensity physical activity, 31,2 % of young men of moderate intensity physical activity, and 61,1 % of boys with high intensity exercise. These findings support the need for careful medical supervision at the stage of sports specialization, as well as during training and competitive periods. The results reflect the optimal interaction of all components of the cardiac rhythm generation in a large part of young men with low-intensity physical activity, indicating that the optimally chosen exercise. The presence of a third of young men with low-intensity physical activity to reduce signs of adaptive capacity demonstrates the importance of medical monitoring of the health of students and the timely adjustment of the intensity of physical training.